The Impact of Transformational and Transactional Leadership on Employee Performance - Wuryaningrat, Nikolas Fajar; Hidayat, Nurul; Kumajas, Merry L. (Faculty of Economics and Business, Universitas Klabat, 2024)
Transformational leadership is a dynamic approach that motivates individuals to work together in achieving organisational goals. It emerges whenever someone exhibits the ability to guide others' behaviours towards a common objective. This leadership style enables leaders to inspire their subordinates positively. The objective of implementing transformational leadership is to improve employee performance within the banking industry in North Sulawesi, Indonesia. The study focuses on three banks, namely Bank BRI, BNI, and BSG, which have branches throughout the North Sulawesi region. A total of 176 employees participated as respondents. Following the collection of data, an analytical method known as Partially Least Squares Structural Equation Modelling (PLS-SEM) was employed for the purpose of analysis. The results provide empirical evidence that transformational leadership has a positive influence on employee performance, particularly in the realms of individual consideration and individual inspiration. Nevertheless, dimensions such as intellectual stimulation and inspirational motivation do not exhibit a significant correlation with performance-related activities. Moreover, the contingent reward aspect of transactional leadership does not demonstrate a significant impact on employee performance.